DEVELOPING SPEAKING FLUENCY THROUGH INTERACTIVE ACTIVITIES IN EFL CLASSROOMS - Ergasheva Ozodabonu Bahodirjon qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: Speaking fluency is a key component of communicative competence in English as a Foreign Language (EFL) learning. This article explores how interactive classroom activities—such as role plays, discussions, games, and information gap tasks—can effectively enhance learners' oral fluency. The study draws on theoretical frameworks of second language acquisition and classroom interaction, supported by practical examples and research findings. Results indicate that interactive activities not only improve fluency but also boost learner motivation, confidence, and communicative competence.